Influences of heat treatment on fatigue crack growth behavior of NiAl bronze (NAB) alloy. Issue 20 (29th September 2015) - Lv, Yuting; Hu, Meng; Wang, Liqiang; Xu, Xiaoyan; Han, Yuanfei; Lu, Weijie
Abstract: Abstract : Fatigue crack growth tests of NiAl bronze (NAB) alloy heat treated at different temper temperature after quenching at 920 °C are performed using direct current potential drop method. The influences of heat treatment on the fatigue crack growth behavior of NAB alloy are investigated. The results show that the fatigue crack growth rate (FCGR) of NAB alloy decreases with the increase of temper temperature. A few large secondary cracks are obtained as the sample is tempered at 350 °C and the secondary cracks diminish with the increase of temper temperature. With further increasing temper temperature to 550 °C, a large number of small secondary cracks are obtained, which is responsible for its lower FCGR. The as-cast NAB alloy has a lower FCGR than that tempered at 550 °C at low stress intensity factor range (Δ K ) region, and the lower FCGR is attributed to the crack deflection effect of the as-cast microstructure. At high Δ K region, the crack deflection effect diminishes, which leads to the higher FCGR of as-cast sample.